Employee Performance Analysis in Enhancing Public Service Quality: a Case Study of Tirtomoyo Subdistrict, Wonogiri Regency, Central Java - Devi Natasari; Sri Wijiastuti; Zandra Dwanita Widodo (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
Public service is a fundamental function of local governments that directly interacts with the community, therefore, service quality is a key indicator of governmental performance. As the frontline administrative unit, the subdistrict plays a strategic role in delivering public services. This study aims to analyze the performance of employees at the Tirtomoyo Subdistrict in improving public service quality from the perspectives of both employees and service users, as well as to identify the supporting and inhibiting factors influencing employee performance. A qualitative research approach was employed, with data collected through interviews and observations. The informants consisted of Tirtomoyo Subdistrict employees and community members as service users, selected through purposive sampling. Data analysis was conducted using NVivo 15 software through systematic coding and thematic analysis. The results indicate that employee performance is generally perceived as good, particularly in terms of service attitude, procedural compliance, work competence, and service implementation quality. Employee performance is strongly associated with improvements in public service quality as perceived by the community. Supporting factors include work motivation, organizational culture, teamwork, leadership support, and employee competence, while inhibiting factors include limited infrastructure, high workload, human resource constraints, and insufficient public understanding of service procedures.